Angiogenin Mutants as Novel Effector Molecules For the Generation of Fusion Proteins With Increased Cytotoxic Potential. Issue 3 (April 2015) - Cremer, Christian; Vierbuchen, Tim; Hein, Lea; Fischer, Rainer; Barth, Stefan; Nachreiner, Thomas
Abstract : Human cytolytic fusion proteins (hCFPs) are therapeutically efficacious recombinant polypeptides comprising a target cell-specific binding component and a human effector domain that induces apoptosis. Compared with former generations of immunotoxins, which contain immunogenic cytotoxic domains derived from bacteria or plants, hCFPs contain solely human proteins that do not induce an immune response, thus avoiding the development of neutralizing antibodies. Here, we investigated the suitability of human angiogenin (Ang) mutants as effector domains. We engineered 3 different Ang variants that outperformed the wild-type enzyme by replacing amino acid residues with key roles in the protein's catalytic activity and its interaction with the ribonuclease inhibitor RNH1. The cytotoxic potential of these mutants was compared with wild-type Ang by fusing each to the CD64-specific single-chain variable fragment H22. All hCFPs were successfully expressed in HEK293T cells and purified from the cell culture supernatant by immobilized metal ion affinity chromatography. The Ang mutant-based hCFPs showed normal binding activity towards human interferon-γ-stimulated CD64 + HL-60 cells and activated human macrophages isolated from peripheral blood mononuclear cells, but increased cytotoxicity based on reduced affinity towards RNH1 and higher ribonucleolytic activity.